Initiating free-flow communication in trust games - Babin, J. Jobu; Chauhan, Haritima S. (Frontiers in Behavioral Economics, 2023)
Theory suggests a first-mover advantage in many strategic bargaining situations, yet often the first to make an offer is not the first to communicate. We report the results of experimental trust games conducted on mobile devices allowing free-flow computer-mediated communication (CMC) rather than pre-play. Free-flow CMC leads to increased trust and overall welfare, where the majority of increased benefit goes to second movers. Using timestamps in chat logs, we find that first-movers most often initiate communication, but there is no direct benefit to doing so. Linguistic analysis of chat logs reveals significant bargaining and screening/signaling content. JEL codes C78, C91, C92, D8, D63, D71.